2022
DOI: 10.1002/jctb.7225
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation reaction mechanism of hydrothermal carbon microspheres with applications to transesterification after sulfonation

Abstract: Background An efficient sulfonic acid‐type acid catalyst with high acid site density based on hydrothermal carbon microspheres (HCMs) has been developed. The reaction by which double bonds in the HCMs were oxidized to generate carboxyl groups was evaluated based on density functional theory calculations. Results Sulfonic acid‐type HCMs (SHCMs) were prepared from HCMs through a three‐step process comprising oxidation, amidation and sulfonation. An analysis of the oxidation process indicated that the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Condensation reactions with and without activation by EDC and NHS were analyzed using density functional theory (DFT) calculations to better understand the activation mechanism. Compared with the results of previous work, 11 the condensation reaction temperature in the present study was lowered by 30 °C and the effect of grafting –NH 2 groups onto the OHCM surfaces was greater.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Condensation reactions with and without activation by EDC and NHS were analyzed using density functional theory (DFT) calculations to better understand the activation mechanism. Compared with the results of previous work, 11 the condensation reaction temperature in the present study was lowered by 30 °C and the effect of grafting –NH 2 groups onto the OHCM surfaces was greater.…”
Section: Introductioncontrasting
confidence: 90%
“…Figure 7 summarizes the effect of the reaction temperature on the yield of FAMEs when using SPEI–EN–OHCMs as a catalyst and demonstrates that the highest yield of 92.3% was obtained at 110 °C after 4 h. The yield of FAMEs obtained in the present study was higher than that of approximately 76% reported by Xue et al . after a reaction at 110 °C for 4 h 11 . This greater yield is primarily ascribed to the activating effect of EDC and NHS on the condensation reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation